Multitemporal Analysis of Potential Geographic Distribution of Lama Guanicoe (SCIÉNDO INGENIUM, 2024)
The purpose of this research is focused on modeling the geographic distribution of Lama guanicoe in South America in two time periods, 2021 and 2070, using MaxEnt software to correlate the bioclimatic variables and calculate the change in the distribution area. Then, with this information, a comparative map of the current and future areas was made in QGIS. As conclusions we can see that in the region of Peru the change of distribution area is reduced, which is observable in the majority of the nations where the guanaco (Lama guanicoe) lives, which is currently considered Endangered, so according to our model it predicts that it will reduce the distribution area by 20%, and the temperature variables have a negative correlation with the area, which indicates that climate change will have a relationship with the Lama guanicoe. This information is necessary for all countries to take action in the conservation of Lama guanicoe by adopting strategies to reduce and prevent climate change, generating and updating their conservation plans.
Keywords: bioclimatic; Maxent; climate change; multitemporal